(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
The SDS-degrading bacterium Pseudomonas sp. strain Maninjau1 experienced significant inhibition by mercury. Observations of bacterial growth at varying mercury concentrations revealed a sigmoidal pattern, with lag periods extending from 7 to 12 hours. Increasing mercury concentrations progressively impeded growth, with a concentration of 1.0 mg/L nearly halting bacterial activity. To analyze these effects, the modified Gompertz model was employed to determine growth rates across different mercury concentrations. These rates were then subjected to several models, including the modified Han-Levenspiel, Wang, Liu, Shukor, modified Andrews, and Amor models. Among these, the Amor model failed to appropriately fit the growth curves. Statistical analysis indicated that the Shukor model performed the best, evidenced by the lowest values for Root Mean Square Error (RMSE) and Akaike’s Information Criterion corrected (AICc), the highest adjusted correlation coefficient (adR2), and values of Accuracy Factor (AF) and Bias Factor (BF) closest to unity. The parameters obtained from the Shukor model, which are mmax (h-1) and Sm (mg L-1) and n which represent maximum growth rate, critical heavy metal ion concentration and empirical constant values were 0.187, 1.126 and 2.406, respectively. The Shukor model allows for the prediction of the critical heavy metals concentration which can completely inhibited bacterial growth. This robust modeling approach underscores the Shukor model’s suitability for predicting the impact of mercury on the growth dynamics of Pseudomonas sp. strain Maninjau1 under toxic stress conditions.